Study of Lazada in Malaysia Reveals the Impact of Social Media Marketing, Brand Trust, And Brand Loyalty on Consumers' Intention to Buy - Intan Nur Nisa; Yee Huei Lok; Rosmelisa Yusof; Intan Nur Syaimaa Binti Mohd Bakri; Iskandar Aliff; Ivy Teoh Ai Wei; Pradhipta Hadyan Mahatmaputra; Dian Nanda Septi Nurawalya; Sachin; Rochana M B (Advances in Global Economics and Business Journal, 2023)
Lazada Group, which was founded in 2012, is the top online shopping platform in Southeast Asia. During the Covid-19 outbreak, a lot of people have switched to electronic purchasing. Online buying is therefore anticipated to become commonplace in the post-pandemic economy. In Malaysia, Lazada seizes the chance and gains market share. This study intends to investigate if social media marketing, brand trust, and brand loyalty can affect Malaysian Lazada users' purchasing intentions. The information was gathered from 150 Lazada users who joined in the online survey through a google form. The results demonstrate social media marketing, brand trust, and brand loyalty influence Lazada users' purchasing intentions. Thus, this study focused on reference and in-intensity understanding of its correlations and a long-term relationship with its customers.